2003
DOI: 10.1002/ejlt.200300796
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability of mayonnaise containing structured lipids produced from sunflower oil and caprylic acid

Abstract: Oxidative stability of mayonnaise containing structured lipids produced from sunflower oil and caprylic acid Mayonnaise based on enzymatically produced specific structured lipid (SL) from sunflower oil and caprylic acid was compared with mayonnaise based on traditional sunflower oil (SO) or chemically randomized lipid (RL) with respect to their oxidative stability, sensory and rheological properties. Furthermore, the potential antioxidative effect of adding lactoferrin, propyl gallate or EDTA to the mayonnaise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…However, the oxidative stability of SL in real foods has only been investigated in a few studies. Previously, we found that the oxidative stability in mayonnaise enriched with SL of MLM-structure produced from sunflower oil and tricaprylin (C8:0) was reduced compared to mayonnaise produced with randomized or traditional sunflower oil [4].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the oxidative stability of SL in real foods has only been investigated in a few studies. Previously, we found that the oxidative stability in mayonnaise enriched with SL of MLM-structure produced from sunflower oil and tricaprylin (C8:0) was reduced compared to mayonnaise produced with randomized or traditional sunflower oil [4].…”
Section: Introductionmentioning
confidence: 97%
“…Previous results had shown that SL would need antioxidants to protect the lipid against oxidation [4,6]. Depending on the kind of oxidation processes dominant in milk drink-type emulsions, different antioxidants may be effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we investigated the antioxidative effect of adding the metal chelators EDTA or citric acid to the SFO. A concentration of 75 mg/kg EDTA was used, since it has been found to work in FO-enriched mayonnaise (6), and an equimolar amount of citric acid (42 mg/kg) was tested.…”
mentioning
confidence: 99%
“…Thus, adequate enrichment levels, shelf life and the addition of antioxidants need to be considered to ensure good quality. Many recent studies have investigated the oxidative stability and sensory stability of omega-3 fatty acids enriched products (Jacobsen et al, 2003(Jacobsen et al, , 2008Dalton et al, 2006;Let et al, 2007;Nielsen et al, 2007;Verardo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%